User interface front end for AFDX test system - Chai, Berwyn Chen Fong (Nanyang Technological University, 2024)
In contemporary aviation systems, the reliability and efficiency of data communication networks are paramount for ensuring the safety and functionality of airborne systems. The Avionics Full-Duplex Switched Ethernet (AFDX) system has emerged as a promising solution, providing deterministic, high-speed communication for critical avionics applications.